A Translation Analysis On Deixis In The Twilight Saga:Breaking Dawn (Book One) By Stephenie Meyer And ItsIndonesian Translation (Pragmatics Perspective) - OktaPrasanti, Ria Tri; , Dr. Anam Sutopo, M.Hum; , Mauly Halwat Hikmat, Ph. D (2014)
This research focuses on analyzing the deixis word found The Twilight Saga: Breaking Dawn (Book One)and its Indonesian translation. The objectives are to describe the type and the function of deixisin the novel Twlight Saga: Breaking Dawn written by Stephenie Meyer and its Indonesian translation Awal yang Baruand to describe equivalence of deixis in the novel Twlight Saga: Breaking Dawn written by Stephenie Meyer and its Indonesian translation Awal yang Baru.This research applies descriptive qualitative method. The data are the deixis word found The Twilight Saga: Breaking Dawn (Book One) and its Indonesian translation. The data source are the novel entitled Twilight Saga: Breaking Dawn (Book One) and its translation "Awal yang Baru". The way to collect data is using docummentation method. The results of the research show that, firstly, there are five types of deixis words found in the novel Twilight Saga: Breaking Dawn (Book One) namely, person deixis, place deixis, time deixis, discourse deixis, and social deixis. From 77 data, there are 32 or 41,56% data belong to personal deixis, 12 or 15,58% data belong to time deixis, 12 or 15,58% data belong to place deixis, 14 or 18,18% data belong to discourse deixis, and 5 or 6,49% data belong to social deixis. It shows the most dominant of acccurance is personaldeixis. Secondly, the equivalence of the data into equivalent translation and nonequivalent translation. From 77 analyzed data, there are 63 or 83,12% data belong to equivalent translation and 13 or 16,88% data belong to non-equivalent translation. So, the translation of deixis word found in Twilight Saga: Breaking Dawn (book one) novel is B which is very good based on grading scale by Machali.